Design of microstrip line-coupled isosceles-triangular loop resonator antenna - Olokede, Seyi Stephen; Mohd Fadzil Ain,; Mohammed Ariff Othman,; Ubaid Ullah,; Zainal Araffin Ahmad, (Fakulti Kejuruteraan ,UKM,Bangi., 2013)
In this paper, an experimental study on a microstrip line proximity coupled triangular microstrip loop resonator antenna is presented. The antenna is fed by a 50 Ω microstrip feed line arrangement at the frequency of 5.8 GHz. The antenna element is placed at λg /4 from the stub, and λg/2 away from the feed based on the voltage allocation on an open ended transmission line where λg is the guided wavelength. The antenna element was rotated 90 degree clockwise about the z-axis in parallel with the microstrip feed. This was done in order to 1) ensure a good proximity coupling, and 2) to indicate that the amount of coupling from the microstrip line to the resonator can be controlled to a certain degree by adjusting the spacing. A similar design was done without rotating the resonator, and the result is reported. It was observed that the measured |S11| of the rotated element is superior to the un-rotated by 43.75%, and 40.43% for the simulated. In all, experimental results agreed significantly with simulated results.